2000
DOI: 10.1046/j.1525-1497.2000.90909.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a decision aid for patients with atrial fibrillation who are considering antithrombotic therapy

Abstract: With patients demanding a greater role in the clinical decisionmaking process, many researchers are developing and disseminating decision aids for various medical conditions. In this article, we outline the essential elements in the development and evaluation of a decision aid to help patients with atrial fibrillation choose, in consultation with their physicians, appropriate antithrombotic therapy (warfarin, aspirin, or no therapy) to prevent stroke. We also outline possible future directions regarding the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…However, there did not appear to be a significant difference in decisional regret (patient's feelings of regret or remorse after a healthcare decision) or the rate of changing from aspirin to warfarin between groups. [49][50][51] It is important to note, however, that the group of patients examined were at low risk of stroke according to the SPAF III trial inclusion criteria and had already been using aspirin for at least 2 years. The decision aid in this case was presented as an audio booklet (which did not individualize the bleeding risk) and an interactive worksheet completed before (but used during) the clinical encounter.…”
Section: Sdm In Thromboembolism Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there did not appear to be a significant difference in decisional regret (patient's feelings of regret or remorse after a healthcare decision) or the rate of changing from aspirin to warfarin between groups. [49][50][51] It is important to note, however, that the group of patients examined were at low risk of stroke according to the SPAF III trial inclusion criteria and had already been using aspirin for at least 2 years. The decision aid in this case was presented as an audio booklet (which did not individualize the bleeding risk) and an interactive worksheet completed before (but used during) the clinical encounter.…”
Section: Sdm In Thromboembolism Preventionmentioning
confidence: 99%
“…The decision aid in this case was presented as an audio booklet (which did not individualize the bleeding risk) and an interactive worksheet completed before (but used during) the clinical encounter. 49,51 More recent SDM studies in AF have reported decreased decisional conflict (the state of uncertainty surrounding a decision, a more accurate measure of the quality of the decision-making process because regret is strongly affected by the outcome the patient experiences, not the communication of the visit), increased patient satisfaction, and a trend toward increased knowledge compared with "traditional counseling" or guideline-based therapies groups, yet the findings have not been consistent. [52][53][54][55][56] Table 3 summarizes the evidence from these studies.…”
Section: Sdm In Thromboembolism Preventionmentioning
confidence: 99%
“…They were also asked to provide written reasons for their choices (aided by a checklist), to complete the Atrial Fibrillation Information Questionnaire again, to indicate their satisfaction with the decision instrument on a 6-point scale and to complete the Decisional Conflict Questionnaire. 31 The Decisional Conflict Questionnaire measures perceptions of personal uncertainty in making a treatment choice, with a lower score indicating more comfort with the decision made; scores higher than 2.5 are associated with decisional conflict.…”
Section: -43mentioning
confidence: 99%
“…[27][28][29][30] It has been reported that they can improve knowledge, reduce decisional conflict and stimulate patients to be more active in decision-making. [31][32][33] However, the jury is still out as to their appropriateness for all patients, their cost-effectiveness and their usability in busy clinical practices or when providers disagree with their advice. [31][32][33] In addition, it is unknown whether the features of decision instruments in terms of their format and content may influence patient decisions.…”
mentioning
confidence: 99%
“…Professional interventions included locally disseminated guidelines, 11-14 stroke orders or protocols, 15-20 a tool to aid clinical decision making 21 ; and training or academic detailing. [22][23][24][25][26][27][28][29][30][31] Primary prevention interventions included information and feedback, 32,33 media campaigns, 34,35 peer support and education, 36 patient decision-aids, [37][38][39] and multifactorial educational, screening and monitoring programs. 40 -47 Secondary prevention interventions included a shared medical record, 48 an intervention incorporating a shared record plus monitoring, 49 and multifaceted interventions incorporating educational and psychosocial components.…”
Section: Redfern Et Al Review Of Complex Interventions In Stroke Carementioning
confidence: 99%